A Light‐Curable and Tunable Extracellular Matrix Hydrogel for In Situ Suture‐Free Corneal Repair. (8th March 2022) - Yazdanpanah, Ghasem; Shen, Xiang; Nguyen, Tara; Anwar, Khandaker N.; Jeon, Oju; Jiang, Yizhou; Pachenari, Mohammad; Pan, Yayue; Shokuhfar, Tolou; Rosenblatt, Mark I.; Alsberg, Eben; Djalilian, Ali R.
Abstract: Corneal injuries are a major cause of blindness worldwide. To restore corneal integrity and clarity, there is a need for regenerative biointegrating materials for in situ repair and replacement of corneal tissue. Here, light‐curable cornea matrix (LC‐COMatrix), a tunable material derived from decellularized porcine cornea extracellular matrix containing un‐denatured collagen and sulfated glycosaminoglycans is introduced. It is a functionalized hydrogel with proper swelling behavior, biodegradation, and viscosity that can be cross‐linked in situ with visible light, providing significantly enhanced biomechanical strength, stability, and adhesiveness. The cross‐linked LC‐COMatrix strongly adheres to human corneas ex vivo and effectively closes full‐thickness corneal perforations with tissue loss. Likewise, in vivo, LC‐COMatrix seals large corneal perforations, replaces partial‐corneal stromal defects and biointegrates into the tissue in rabbit models. LC‐COMatrix is a natural ready‐to‐apply biointegrating adhesive that is representative of native corneal matrix with potential applications in corneal and ocular surgeries. Abstract : A light‐curable hydrogel is fabricated from decellularized porcine cornea extracellular matrix with tunable biomechanical and bioadhesive properties. The light‐curable cornea matrix (LC‐COMatrix) has appropriate viscosity for upright application on the injured cornea in an office. LC‐COMatrix is cytocompatible and effectively repairs corneal stromal and corneal perforation injuries.